2014
DOI: 10.1186/2047-783x-19-5
|View full text |Cite
|
Sign up to set email alerts
|

Association of methylenetetrahytrofolate reductase (MTHFR) C677T and A1298C polymorphisms with the susceptibility of childhood acute lymphoblastic leukaemia (ALL) in Chinese population

Abstract: BackgroundThe aim of this study was to investigate the relationship between the polymorphisms of the methylenetetrahytrofolate reductase (MTHFR) gene and susceptibility to childhood acute lymphoblastic leukemia (ALL).MethodsA case–control study was conducted among 98 children with ALL and 93 age- and sex- matched non-ALL controls. Genotyping of MTHFR C677T and A1298C polymorphisms was performed by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP). The odds ratios (ORs) of MTHFR geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 23 publications
0
5
2
Order By: Relevance
“…In addition, frequencies of MTHFR 1298AA, 1289A>C, and 1298CC were significantly different in those two groups. However, no significant different in frequencies of MTHFR 677CC, 677C>T, and 677TT genotypes were observed in this report (Li et al, 2014). Moreover, MTHFR 1298A>C genotype and the 677CC/1298A>C haplotype were significantly associated with reduced the risk of acute myeloid leukemia (AML) compared with AA genotype and 677CC/1298AA haplotype.…”
Section: Introductioncontrasting
confidence: 64%
“…In addition, frequencies of MTHFR 1298AA, 1289A>C, and 1298CC were significantly different in those two groups. However, no significant different in frequencies of MTHFR 677CC, 677C>T, and 677TT genotypes were observed in this report (Li et al, 2014). Moreover, MTHFR 1298A>C genotype and the 677CC/1298A>C haplotype were significantly associated with reduced the risk of acute myeloid leukemia (AML) compared with AA genotype and 677CC/1298AA haplotype.…”
Section: Introductioncontrasting
confidence: 64%
“…These findings are consistent with previous research that identified the T allele to be a protective factor [ 21 , 22 , 29 36 ], but not with those studies which identified the T allele as a risk factor [ 37 39 ]. Additionally in some studies the T allele has been shown to have no association with childhood ALL [ 40 54 ]. Table 4 contains a summary of the findings from all of the literature investigating the association between MTHFR genotypes and childhood leukemia risk with a representative sample size (control/case larger than 70/70) and a non-redundant population.…”
Section: Discussionmentioning
confidence: 99%
“…Among the studies, allele T was associated with decreased risk in populations of Taiwan, Serbia, China, Netherlands, Greece, Canada, and UK [ 22 , 30 32 , 34 , 36 ], while with increased risk in populations of India [ 38 ]. Others proposed that the T allele was not associated with childhood ALL [ 40 54 ]. However, even the people in the same country, for instance Brazil, there was a dramatically different susceptibility to cancer, showing both decreased [ 21 , 35 ] and increased risk [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the inclusion/exclusion criteria, 12 case-control studies (11 articles) [12,13,14,15,16,17,18,19,20,21,22] were included and 103 articles were excluded. The publication year of the included studies ranged from 2004 to 2014.…”
Section: Resultsmentioning
confidence: 99%